Nutrients and biomass quantification in Eucalyptus dunnii Maiden stand established in Pampa biome - Dick, Grasiele; Schumacher, Mauro Valdir; Momolli, Dione Richer; Santos, Joel Carvalho dos; Ludvichak, Aline Aparecida; Guimarães, Claudiney Couto; Souza, Huan Pablo de (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
Studies related to biomass production and accumulation of nutrients, are the basis for understanding the nutritional dynamics in forest stands. The objective of this study was to quantify the biomass and nutrient stocks, in a Eucalyptus dunnii stand, at 60 months old, established in Alegrete, Rio Grande do Sul. The sampling of biomass was taken from twelve trees which were cut at soil level and the fractional biomass components: leaf, branches, trunk bark and stem wood, with dry mass determination and nutrients concentration. The total above ground biomass was 58.76 Mg ha-1, with decreasing sequence in the magnitude of the stem wood > trunk bark > branches > leaves. The total stock of nutrients was 175.5; 18.2; 171; 278.1; 69.1 and 21.5 kg ha-1 of N, P, K, Ca, Mg and S, respectively. We emphasize the importance of maintaining of harvest residues in the soil to optimize nutrient cycling due to high levels of these in the leaves, bark and branches.